2016
DOI: 10.1111/odi.12442
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of CD44v6, p63, podoplanin and MMP‐9 in oral squamous cell carcinomas

Abstract: Podoplanin and MMP-9 together could contribute to tumour progression and dissemination of OSCC. Their combined overexpression showed an adverse effect on survival, suggesting that they could be regarded as important prognostic biomarkers in OSCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
50
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(66 citation statements)
references
References 52 publications
(102 reference statements)
7
50
0
7
Order By: Relevance
“…MMP‐9 is known to induce tumor angiogenesis, a key factor in tumor progression . Studies have reported a relationship between MMP‐9 expression and the prognosis of patients with oral cancer . Katayama et al and Kosunen et al demonstrated that overexpression of MMP‐9 is associated with cervical lymph node metastasis, an advanced clinical stage, and poor tumor differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…MMP‐9 is known to induce tumor angiogenesis, a key factor in tumor progression . Studies have reported a relationship between MMP‐9 expression and the prognosis of patients with oral cancer . Katayama et al and Kosunen et al demonstrated that overexpression of MMP‐9 is associated with cervical lymph node metastasis, an advanced clinical stage, and poor tumor differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…The inflammatory markers TAN, MMP‐9, and IL‐17 have been individually proposed as prognostic biomarkers in oral squamous cell carcinoma (OSCC) . Garley et al and Li et al observed that the supernatants and blood serum of patients with oral cancer exhibit higher concentrations of IL‐17 than those of healthy subjects, and this difference is associated with tumor growth and metastasis .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, OSCC patients with elevated TP63 levels have a poorer survival rate. However, inconsistent results regarding the association of TP63 expression with OSCC patient prognosis have also been described [39]. These conflicting results may be attributed to the different demographic characteristics, anatomic sites [40], and spatiotemporal expression patterns of the TP63 isoforms in patients with OSCC.…”
Section: Discussionmentioning
confidence: 99%